Image-based assessment of esophageal stricture in experimental corrosive esophagitis in animals: An objective, adjunct diagnostic tool - Enver VARDAR; Rukiye VARDAR; Vahit YÜKSELEN; Özer MAKAY; Nazif ERKAN; Ümit BAYOL; Ömer ÖZÜTEMİZ (Turkish Journal of Gastroenterology, 2019)
-